ASSESSMENT OF FORECAST PARAMETERS OF THE AVERAGE LONG-TERM WATER FLOW FORMED IN LARGE COLLECTORS - Ravshan Aminaddinovich Mamutov (Modern American Journals, 2025)
The assessment of forecast parameters of the average long-term water flow formed in collector–drainage networks, as well as the quantitative parameters of water resources accumulated in main collectors, and the improvement of hydraulic methods for discharging certain portions of these waters into irrigation canals, are among the urgent scientific and technical challenges.This article presents the results of assessing the quantitative parameters of water resources accumulated in the Daryalyk Main Collector in the Khorezm region, as well as the forecast parameters of the average long-term water flow formed in the Divankul Collector.
Keywords: Collector–drainage networks, water mineralization, water discharge, flow, hydrological post, forecast parameters of water flow, empirical curve.